The Status of Witchcraft in the Modern World - Hutton, Ronald (Pomegranate, 2007)
Contemporary Pagan Witches have for the most part abandoned the foundation myth that they represent the survival of an ancient religion forced underground during the era of European witch trials. They have transformed older models of witchcraft to serve the needs of modern spirituality. Yet those same older models present problems to publics and governments around the world, where witchcraft persecutions and panics over ’ritual abuse’ continue. Scholars of historical witch trials still have a role to play in educating people about the psychological realities of witchcraft and the dangers of panic and persecution.